Skrining Penyakit Diabetes Melitus Dengan Pemeriksaan Gula Darah Sewaktu Pada Lansia Di Desa Sumberjambe Kabupaten Jember - Syahrial Dwi Meidiansyah; Maralodia Almira Lubis; Dhea Adelina Br Ginting; Wulan Ratna Nur Kholidiya; Muhammad Rizky Suryadinata; Nur Halimatus Sa’diyah; Aisyah Salsabila Oktivani Yunita; Faidatur Rohma; Taufiki Nurul Yahya; Maimunah Maimunah; Sulton Auliya; Alisa Alfiya Makki; Alisyah Pratiwi; Cahyaning Dewi Kusuma Wardani; Diana Nadhifah; Ayu Tri Agustin (FKIP, Universitas Palangka Raya, 2024)
Diabetes mellitus (DM) is a disease caused by excessive levels of sugar in the blood due to a lack of the hormone insulin. DM screening is done because there are some residents who have the disease. This examination is specifically for the elderly because they also have the potential to be infected without being detected. The activity was carried out using two methods, namely socialization and followed by blood pressure and random blood sugar checks which were carried out in two hamlets, namely Slangak and Semek hamlets. The results of the screening showed that 14.29% of the participants had sugar levels > 200 mg/dl, which means that there is a DM factor, so it is necessary to do short-term prevention to control DM disease.